2017
DOI: 10.1159/000480537
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Probe Placement during Preterm Infant Resuscitation: A Randomised Trial

Abstract: Background: Hypothermia on admission to intensive care is associated with poor outcomes in preterm infants. The neonatal resuscitation program recommends the use of servo-control thermoregulation during resuscitation. Very little evidence exists to guide optimal temperature probe placement in the delivery room. Objective: The aim of this work was to determine, in moderately preterm infants, if temperature probe placement in the dorsal, thoracic, or axillary area during delivery room resuscitation would result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…3 Variation in practice exists for the site of securing a temperature probe during DR stabilization. 9 Bensouda et al found comparable body temperatures at admission to the NICU when three different sites of temperature probe positioning (left lower back, left upper thorax, and left axilla) were compared in preterm infants ≥28 weeks GA. 10 In our unit, despite an improvement in normothermia after introducing a thermoregulation bundle for very preterm infants (<32 weeks GA) during DR stabilization, some infants continued to develop hypothermia. 11 The current study was designed to test the hypothesis that application of a temperature probe to the left upper back during DR stabilization will achieve a higher proportion of normothermia at the time of NICU admission than application in the left axilla in very preterm infants.…”
Section: Introductionmentioning
confidence: 70%
“…3 Variation in practice exists for the site of securing a temperature probe during DR stabilization. 9 Bensouda et al found comparable body temperatures at admission to the NICU when three different sites of temperature probe positioning (left lower back, left upper thorax, and left axilla) were compared in preterm infants ≥28 weeks GA. 10 In our unit, despite an improvement in normothermia after introducing a thermoregulation bundle for very preterm infants (<32 weeks GA) during DR stabilization, some infants continued to develop hypothermia. 11 The current study was designed to test the hypothesis that application of a temperature probe to the left upper back during DR stabilization will achieve a higher proportion of normothermia at the time of NICU admission than application in the left axilla in very preterm infants.…”
Section: Introductionmentioning
confidence: 70%
“…The skin temperature measured with a probe under an occlusive, reflective patch is well correlated with the core temperature and can be monitored as a reliable, alternative guide to the body's temperature when necessary 19,20 . Furthermore, the part of the trunk, axillary, flank or back to which the probe is attached appears to have little to no influence on the temperature value when the said probe is placed under an occlusive, reflective patch 23 . The use of two skin probes allows the detection of probe detachments and the monitoring of the gradient between core and peripheral temperatures 2,24 .…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Furthermore, the part of the trunk, axillary, flank or back to which the probe is attached appears to have little to no influence on the temperature value when the said probe is placed under an occlusive, reflective patch. 23 The use of two skin probes allows the detection of probe detachments and the monitoring of the gradient between core and peripheral temperatures. 2,24 The peripheral temperature is then measured on the end of a limb, with the probe again covered by a reflective patch.…”
Section: How Should the Newborn Infant's Body Temperature Be Monitored?mentioning
confidence: 99%
“…Bensouda et al recorded similar admission temperatures in moderate preterm infants from temperature-probe placement on the axilla, left upper and left lower back. 17 A single centre randomised control trial in Australia is currently recruiting preterm infants <32 weeks gestation to ascertain the effect of temperature-probe placement in the axilla compared to the left upper back during delivery room resuscitation on admission body temperature (ACTRN12620000293965).…”
Section: Discussionmentioning
confidence: 99%